Mk 1:1 and the Debate on a 'Markan Prologue' - Becker, Eve-Marie 1972- (2009)
On the basis of observations to the syntactical structure and the literary style of Mk 1:1-15 as well as to the literary genre of the Markan Gospel, this paper questions those concepts of subdividing Mk 1 according to which Mk 1:1-13/15 is classified as a 'Markan prologue'. It is argued instead, that already Mk 1:4 opens up the Gospel narration and that only Mk 1:1-3 has to be regarded as a literary unity: Mk 1:1-3, however, is in no case part of a 'Markan prologue' or a 'prologue' in itself. These verses are rather more to be understood as a prooemium to the overall prose-text of the Gospel narrative, consisting of a 'Buchüberschrift'/title (1:1) and an opening introductory close (1:2-3).
Keywords: Mark 1,1; Prologue of Mark